Early Detection of Colorectal Cancer Recurrence in Patients Undergoing Surgery with Curative Intent: Current Status and Challenges - Young, Patrick. E. (Ivyspring International Publisher, 2014)
Despite advances in neoadjuvant and adjuvant therapy, attention to proper surgical technique, and improved pathological staging for both the primary and metastatic lesions, almost half of all colorectal cancer patients will develop recurrent disease. More concerning, this includes ~25% of patients with theoretically curable node-negative, non-metastatic Stage I and II disease. Given the annual incidence of colorectal cancer, approximately 150,000 new patients are candidates each year for follow-up surveillance. When combined with the greater population already enrolled in a surveillance protocol, this translates to a tremendous number of patients at risk for recurrence. It is therefore imperative that strategies aim for detection of recurrence as early as possible to allow initiation of treatment that may still result in cure. Yet, controversy exists regarding the optimal surveillance strategy (high-intensity vs. traditional), ideal testing regimen, and overall effectiveness. While benefits may involve earlier detection of recurrence, psychological welfare improvement, and greater overall survival, this must be weighed against the potential disadvantages including more invasive tests, higher rates of reoperation, and increased costs. In this review, we will examine the current options available and challenges surrounding colorectal cancer surveillance and early detection of recurrence.